Obnova Starého Brna - Sopoušková, Petra (Vysoké učení technické v Brně. Fakulta architektury)
Práce se zabývá vývojem Starého Brna. Staré Brno je v současnosti poznamenáno čekáním na realizaci územního plánu, který by měl vyřešit problém příliš velké dopravní zátěže oblasti. Na realizaci se však pravděpodobně bude čekat několik desítek let. Navrhuji využít časového úseku před změnou dopravy a započít postupný vývoj, který by předznamenával cílovou podobu městské části. Dobře fungující město nelze vytvořit jen kvalitně navrženou architekturou a urbanismem. Proto navrhuji proces, který by měl vést k cílové podobě, ale vytvářet sociálni, ekonomické, ekologické a estetické hodnoty nezávisle na ní. Pro tyto účely využívám prázdné plochy a dočasné stavby.

The work deals with the development of the Old Brno District . Old Brno District is currently marked by waiting for the implementation of the land use plan, which should solve the problem of traffic. The implementation, however, will probably take a few decades. I propose to use the period of time before the change of traffic routes and begin a gradual development that will prefigure target form of the district. Well-designed architecture and urbanism is not the only condition for well-functioning city. Therefore, I propose a process which should lead to the target form, but to create social, economic, ecological and aesthetic values independently of it. For this purpose vacant spaces and temporary structures are used.
Renewal of Old Brno District
Keywords: Staré Brno; brownfield; nevyužívaná místa; dočasná stavba; proces; postupný vývoj; Old Brno District; brownfield; vacant spaces; temporary structures; process; gradual development